Occupational Hazards Knowledge among a Sample of Medical and Paramedical Staff in Baghdad City - Sajjad M. hasan; Suhair M. Hassoun; Luma H. Ali (Journal of Techniques)
Occupational hazards include any behaviors which possess the potential to cause or raise risks at the workplace, as well as the compounding effects of accidents and occupational diseases within workers in the health and medical field. As a result, such hazards have a deleterious impact on staff, their families and friends, and the country. To identify the levels of knowledge of medical and paramedical staff regarding occupational hazards in their workplaces.